CRIMINAL ACTS HANDLING: THE CONCEPT OF CRIMINAL LAW REFORM - Purnamasari, Andi Intan; Awaliyah, Awaliyah; Utami, Fidyah Paramita (Tadulako Master Law Journal, 2021)
Data shows that 24 cases in Central Sulawesi in 2019 were all sentenced to prison or imprisonment which is still the favorite type of sanction. How not, even 18 of the 24 cases did not need to serve a period of detention, but underwent various probationary periods, at least 1 month of probation and a maximum of 12 months. However, it needs to be realized that if the imposition of this criminal sanction does not need to be implemented, why should it impose sanctions in the form of conventional punishment, the answer is of course because the legality principle only gives room to the criminal, so it is necessary to have an alternative description of what the maker can use the law in formulating the sanctions for resolving election criminal acts as an effort to redesign the model for tackling election crime in Indonesia, particularly in the Central Sulawesi region. The issue in this research covers criminalization in case study election crimes in Central Sulawesi with the perspective of ius constitutum and alternative punishment in case study election crimes in central Sulawesi from the perspective of ius constituendum. The research method uses normative juridical research methods. The results achieved are that the type of Election Crime as an ius constitutum still uses the conventional system, so to achieve the ius constituendum it is necessary to modify the sanctions in the form of alternative types of sanctions that are more efficient, such as the cancellation sanction as a candidate for candidate in the election contest.